2010
DOI: 10.1371/journal.pntd.0000668
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of Basic Lymphedema Management in Leogane, Haiti, an Area Endemic for Bancroftian Filariasis

Abstract: BackgroundApproximately 14 million persons living in areas endemic for lymphatic filariasis have lymphedema of the leg. Clinical studies indicate that repeated episodes of bacterial acute dermatolymphangioadenitis (ADLA) lead to progression of lymphedema and that basic lymphedema management, which emphasizes hygiene, skin care, exercise, and leg elevation, can reduce ADLA frequency. However, few studies have prospectively evaluated the effectiveness of basic lymphedema management or assessed the role of compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
65
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 36 publications
7
65
2
Order By: Relevance
“…These findings are consistent with other studies which have also found a decrease in ADLA episodes following enrollment in a lymphedema management program [2], [3], [13], [14], [23], [24]. Other programs have found a similar plateauing of the ADLA rate 3–12 months after beginning lymphedema management [13], [14]. Although our results show a significant decrease in the rate of ADLA episodes over the 2 years since the lymphedema management program was implemented, we recognize that this decrease may be partially influenced by patient receipt of anti-filarial drugs during the two MDAs that took place over the course of the study [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with other studies which have also found a decrease in ADLA episodes following enrollment in a lymphedema management program [2], [3], [13], [14], [23], [24]. Other programs have found a similar plateauing of the ADLA rate 3–12 months after beginning lymphedema management [13], [14]. Although our results show a significant decrease in the rate of ADLA episodes over the 2 years since the lymphedema management program was implemented, we recognize that this decrease may be partially influenced by patient receipt of anti-filarial drugs during the two MDAs that took place over the course of the study [21].…”
Section: Discussionsupporting
confidence: 93%
“…The study in Léogâne, Haiti found that compliance was associated with female gender and age >40 years [13], two associations we did not find. Patients enrolled in the limb-care program in Sri Lanka identified inconvenience, inability to find footwear large enough to fit, and forgetting to exercise the affected limb as the main reasons for non-compliance to the limb-care program [27].…”
Section: Discussioncontrasting
confidence: 85%
“…Among individuals aged 15 and older who reported lymphedema, older age (70 years and older) was highly associated with an increased prevalence of advanced stage lymphedema; which is consistent with findings in other LF endemic areas, such as Haiti [24]. The increase in prevalence of lymphedema with increasing age corresponds to the fact that lymphedema symptoms often do not appear until years or even decades after an individual is first infected and they tend to worsen over time and with the number of ADL episodes a person experiences.…”
Section: Discussionsupporting
confidence: 84%
“…The use of CDT to reduce lymphedema was used in an endemic area, as shown in the study conducted in Haiti by Addiss et al 24 .…”
Section: Discussionmentioning
confidence: 99%